2020
DOI: 10.1007/s00261-020-02693-2
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adipose tissue in patients with COVID-19: risk stratification for severity

Abstract: Purpose To assess visceral (VAT), subcutaneous (SAT), and total adipose tissue (TAT) estimates at abdominopelvic CT in COVID-19 patients with different severity, and analyze Body Mass Index (BMI) and CT estimates of fat content in patients requiring hospitalization. Methods In this retrospective IRB approved HIPPA compliant study, 51 patients with SARS-CoV-2 infection with abdominopelvic CT were included. Patients were stratified based on disease severity as outpatient (no hospital admission) and patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 24 publications
3
62
1
Order By: Relevance
“…Yang et al did not identify SFA > 100 mm 2 as a risk factor for ICU admission (OR = 1.06, 95% CI: 0.52‐2.17) (32). However, a high VFA/SFA ratio was found to be associated with an increased risk for ICU admission (OR = 2.47, 95% CI = 1.05‐5.98) (9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yang et al did not identify SFA > 100 mm 2 as a risk factor for ICU admission (OR = 1.06, 95% CI: 0.52‐2.17) (32). However, a high VFA/SFA ratio was found to be associated with an increased risk for ICU admission (OR = 2.47, 95% CI = 1.05‐5.98) (9).…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta‐analysis by Huang et al has come to the same conclusion (20); they have found higher VAT values in patients with critical condition, as well. However, their search interval was shorter, and we included two additional studies in the meta‐analyses (9,11). They did not change the direction of the results but rather confirmed the previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, studies investigating the role of body fat distribution on the severity and susceptibility of COVID-19 are scarce. Few observational studies investigated the association between visceral fat and COVID-19 disease severity and complications and suggested that abdominal fat is related to disease severity 29-33 . For example, in their proof-of-concept study including 30 patients with COVID-19 Petersen et al suggested that visceral fat and upper abdominal circumference specifically increased the likelihood of severe COVID-19 31 .…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Although BMI is widely used to diagnose obesity, 10 further phenotyping of patients with high BMI might improve risk stratification and help to reveal the underlying pathophysiology. [11][12][13][14][15][16] In summary, we are grateful to Liu et al…”
mentioning
confidence: 94%